Disability status and multi-dimensional personal well-being among adolescents in the Southern Highlands Region of Tanzania: results of a cross-sectional study - Karen Devries; Tia M Palermo; Hannah Kuper; Leah Prencipe; Tia Palermo; Atif Khurshid; Lusajo Kajula; Jacobus de Hoop; Valeria Groppo; Johanna Choumert Nkolo; Respichius Mitti; Bhoke Munanka; et al. (BMJ Open, 2021)
Objective Examine how disability status among adolescents is associated with the following domains of personal well-being: schooling, livelihoods, health, violence and psychosocial well-being. It is hypothesised that adolescents with a disability will have greater deficits in these areas of well-being compared with their healthier counterparts.Design Cross-sectional data from 2018 were obtained from the second round of an on-going study of adolescents living in poor households in two regions of the Southern Highlands of Tanzania (Iringa and Mbeya). We use the Washington Group (WG) Short Set indicators to measure disability and undertook logistic and linear multivariate regressions to understand the association between disability and the outcomes of interest.Participants The sample included 2274 participants aged 15–20 years living in households participating in a government social protection programme targeted to households living in extreme poverty.Results Overall, 310 participants (14%) were classified as having disabilities. Outcomes not associated with disability status included literacy, schooling, livelihoods and self-efficacy. Adolescents with disabilities were less likely to report good or very good health (adjusted OR (aOR)=0.39, 95% CI 0.29 to 0.52) and had increased odds of reporting depressive symptoms in (aOR=1.46, 95% CI 1.11 to 1.90), emotional violence (aOR=2.18, 95% CI 1.49 to 3.20) and physical violence (aOR=1.71, 95% CI 1.13 to 2.59), compared with those without disabilities. Reports of depression were higher among men, and violence was more prevalent among women. Patterns of association were generally similar between men and women, although the association of disability with markers of well-being reached statistical significance more often among men.Conclusion This study highlights areas where adolescents with disabilities are falling behind their peers in terms of personal well-being. These findings suggest that interventions may be needed to mainstream disability in programmes and policies aiming to improve well-being, mental health and violence prevention among adolescents.Trial registration number Pan African Clinical Trial Registry (PACTR201804003008116).